Fiscal volatility, financial crises and growth - Afonso, António (2012)
We use a panel of developed and emerging countries for the period 1970-2008 to assess how fiscal policy volatility and financial crises affect growth. We find that economic growth is lower in the presence of more volatile fiscal policy. Moreover, with a financial crisis government spending is stickier than revenue.